Test Anxiety, Coping, Gender and Academic Performance in English Exams: A Study of Finnish Upper Secondary School Students - Green, Emily (My University, 2016)
In this MA thesis, test anxiety related to English exams among Finnish upper secondary school students was studied. In addition, the ways students try to cope with test anxiety were investigated. The purpose of the study was to investigate gender differences in test anxiety, the effects of test anxiety on academic performance and relationships between test anxiety, academic performance and coping strategies. Test anxiety and coping strategies were analysed as scores of questionnaire responses. Coping strategies comprised of three categories – task-orientation and preparation, seeking social support and avoidance. Academic performance was analysed as teacher ratings of general performance in English exams. In total 67 subjects were studied. The subjects were Finnish general upper secondary school students. The data were collected by using online questionnaires. This data were mainly quantitative, but also qualitative elements were included. The quantitative data were analysed by using statistical methods. The results showed that females experienced statistically significantly more test anxiety than males. In addition, a statistically significant correlation was found between test anxiety levels and academic performance ratings of the subjects: the higher the test anxiety score, the lower the academic performance rating. A meaningful correlation was found between test anxiety and seeking social support as a coping strategy: a higher test anxiety score was related to using social support as a coping strategy. However, no relationships were found between academic performance and the three coping strategies when quantitative and qualitative data were analysed. Therefore, different coping strategies per se did not seem to be related to academic performance, but instead it was assumed that the effectiveness of coping strategies is dependent on individual differences. In order to obtain more generalisable results and to gain more understanding of test anxiety and coping with it, a larger number of subjects form different areas of Finland and of different ages could be examined in future studies. Moreover, cross-national and cross-cultural studies could provide valuable information. As a practical recommendation for educational purposes, the results of this study indicated that a more individualised approach is needed.